Evaluation of a Pilot Program to Increase Mental Health Care Access for Youth—The Interprofessional Child-Centered Integrated Care (ICX2) Model - Nicole Klaus; Evelyn English; Elizabeth Lewis; Jordan Camp; Sarah Krogman; Kari Harris (Children)
Background/Objectives: The pediatric mental health crisis in the United States has reached unprecedented levels. Severe shortages in specialized health care professionals, particularly child and adolescent psychiatrists (CAPs), exacerbate the challenge of delivering timely and quality mental health care, especially in rural areas like Kansas. Innovative models such as Pediatric Mental Health Care Access (PMHCA) programs and School-Based Health Clinics (SBHCs) aim to integrate mental health expertise into primary care settings to address this gap. Methods: This paper examines an integrated care model to support SBHCs developed by the Kansas PMHCA. The Interprofessional Child-Centered Integrated Care Model (ICX2) was implemented within an SBHC in Haysville, KS. ICX2 utilizes biweekly collaborative team meetings (CTMs) via zoom involving primary care, psychology, child psychiatry, social work, and school resource coordinators to discuss patient cases and enhance the primary care management of pediatric mental health. This descriptive study analyzes data from January 2023 to June 2023, focusing on patient demographics, case characteristics discussed during CTMs, and recommendations made by the interprofessional team. Results: Findings illustrate the complex biopsychosocial needs of patients seen and define themes of case consultation and recommendations. Conclusions: Integrated care programs like ICX2 can be feasibly implemented through PMHCA programs and may be an efficient intervention to bridge resource gaps.